2016
DOI: 10.1080/19485565.2015.1124325
|View full text |Cite
|
Sign up to set email alerts
|

An Old Mom Keeps You Young: Mother’s Age at Last Birth and Offspring Longevity in Nineteenth-Century Utah

Abstract: This study analyzes the intergenerational effects of late childbearing on offspring's adult longevity in a population in Utah (United States) that does not display evidence of parity-specific birth control-a so-called natural fertility population. Studies have found that for women who experience late menopause and prolonged reproduction, aging is postponed and longevity is increased. This is believed to indicate female "robustness" and the impact of biological or genetic factors. If indeed there is a genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Before age 5, offspring of long-lived fathers had a smaller survival advantage of 7%. The survival advantage enjoyed by offspring of long-lived mothers remained roughly 20%, but was modest in comparison to known additive effects of high infant mortality in the sibship (Broström, Edvinsson & Engberg, 2018;Hin, Ogórek & Hedefalk, 2016;Janssens, Messelink & Need, 2010;Sommerseth, 2018;, descending from a small family (Doblhammer & Oeppen, 2003), parental birth spacing (Dewey & Cohen, 2007;Kozuki et al, 2013), or having a farming father (Breschi et al, 2011;Edvinsson et al, 2005;Janssens & Pelzer, 2012;Schumacher & Oris, 2011;Van Poppel, Jonker & Mandemakers, 2005). However, the survival advantage enjoyed by offspring of long-lived parents is indicative of one of the mechanisms behind child mortality.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Before age 5, offspring of long-lived fathers had a smaller survival advantage of 7%. The survival advantage enjoyed by offspring of long-lived mothers remained roughly 20%, but was modest in comparison to known additive effects of high infant mortality in the sibship (Broström, Edvinsson & Engberg, 2018;Hin, Ogórek & Hedefalk, 2016;Janssens, Messelink & Need, 2010;Sommerseth, 2018;, descending from a small family (Doblhammer & Oeppen, 2003), parental birth spacing (Dewey & Cohen, 2007;Kozuki et al, 2013), or having a farming father (Breschi et al, 2011;Edvinsson et al, 2005;Janssens & Pelzer, 2012;Schumacher & Oris, 2011;Van Poppel, Jonker & Mandemakers, 2005). However, the survival advantage enjoyed by offspring of long-lived parents is indicative of one of the mechanisms behind child mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Associations between family fertility histories and offspring survival have been less thoroughly studied. Hin, Ogórek, and Hedefalk (2016) reported that having a late-reproducing mother or fewer siblings associated with increased survival after age 50. However, we found no evidence that having a late-reproducing mother, lower birth order, longer birth intervals, or younger parents associated with offspring survival associated with offspring survival between ages 5-100.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations